ANALISIS KEPRIBADIAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PEGAWAI KECAMATAN BANGIL KELURAHAN DERMO KABUPATEN PASURUAN - Rahmawan, Adhiansyah; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of personality and competence on employee performance, both directly and through work motivation as a mediating variable, among employees of the Bangil District Office, Pasuruan Regency. This research adopts a quantitative approach with a population and sample consisting of 35 employees, using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the assistance of SmartPLS 3.0 software. The results of the study indicate that: (1) Personality has a significant influence on employee performance; (2) Competence has a significant influence on employee performance; (3) Work motivation significantly influences employee performance; (4) Personality influences employee performance through work motivation; and (5) Competence influences employee performance through work motivation. These findings suggest that enhancing personality and competence, either directly or through increased work motivation, can improve employee performance in public institutions.